(untitled) (Universal International Scientific Journal, 2026)
This article discusses the pedagogical and psychological significance of using game technologies in primary education. The role of game technologies in consolidating students’ knowledge, developing their independent and creative thinking, and increasing their interest in the lesson is analyzed. The impact of game methods on educational effectiveness is also substantiated.